2016
DOI: 10.1163/22125868-12340070
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Internship on Job Performance among University Graduates in South Korea

Abstract: This study aims to explore internship experiences and their influence on job performance among university graduates in Korea. The research questions are as follows: 1) To what extent do university students engage in different types of internships in Korea? 2) How do internship experiences differ by academic fields and institutional types? 3) Does internship experience predict graduates’ job performance, namely their job search duration, wages, and job satisfaction? This study used the Korean Education and Empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
2
30
0
1
Order By: Relevance
“…Findings revealed that all participants, regardless of whether they had completed an internship, believed doing so was valuable. They described feeling some pressure to complete internships on their campus, which aligns with the broader landscape within higher education that has pushed for internship completion to prepare undergraduate students to transition to work (e.g., Jung & Lee, 2017;Silva et al, 2018). Participants believed that completing internships would lead beneficial outcomes and that internship completion provide opportunities to learn, practice, and apply skills while gaining career and life experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings revealed that all participants, regardless of whether they had completed an internship, believed doing so was valuable. They described feeling some pressure to complete internships on their campus, which aligns with the broader landscape within higher education that has pushed for internship completion to prepare undergraduate students to transition to work (e.g., Jung & Lee, 2017;Silva et al, 2018). Participants believed that completing internships would lead beneficial outcomes and that internship completion provide opportunities to learn, practice, and apply skills while gaining career and life experience.…”
Section: Discussionmentioning
confidence: 99%
“…The National Association of Colleges and Employers estimated that 65% of graduating college students in the U.S. completed an internship or a co-op program in 2016 (Crain, 2016) as compared to 3% in the 1980's (Perlin, 2011). The emphasis on internships has increased as higher education institutions have been tasked with addressing post-graduate employment (Silva et al, 2018) and with preparing students for the challenges of the changing job market (Jung & Lee, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…approaches to learning (Jung and Lee, 2017). Students often use internships as a way to test out career options, due to which they lead to improved job satisfaction by better preparation for entering work.…”
Section: Grade Point Average (Gpa)mentioning
confidence: 99%
“…Sahada yapılan uygulamalar, stajyerlerin mesleki alan deneyimlerini arttırması nedeniyle önemlidir. Stajyerlik deneyimi, iş bulma, daha iyi ücret ve Aralık 2018 Cilt 20 Sayı 2 (119-133) DOI: 10.26468/trakyasobed.427663 mesleki doyum noktasında bireylerin mesleki performansını geliştirmektedir (Jung ve Lee, 2017). Fakat bu süreçlerde, yaşanan sorunlar stajyerlerin mesleki deneyimlerine yönelik isteklerini olumsuz şekilde etkiyebilmektedir.…”
Section: ġģE Ve ġģYerine Uyum Temasıunclassified